№1 Введем замену ![5x+3y=a\ \ \ \ \ \frac{4}{7x-}=b 5x+3y=a\ \ \ \ \ \frac{4}{7x-}=b](https://tex.z-dn.net/?f=5x%2B3y%3Da%5C+%5C+%5C+%5C+%5C+%5Cfrac%7B4%7D%7B7x-%7D%3Db)
сложим первое и второе уравнения
![2a=8\\\ a=4\ \ b=1 2a=8\\\ a=4\ \ b=1](https://tex.z-dn.net/?f=2a%3D8%5C%5C%5C+a%3D4%5C+%5C+b%3D1)
Вернемся к замене
\ \left \{ {{5x+3y=4} \atop {7x-y=4}} \right.\ <=>\ \left \{ {{5x+3y=4} \atop {y=7x-4}} \right.\ <=>\\\ <=>\ \left \{ {{5x+3(7x-4)=4} \atop {y=7x-4}} \right.<=>\ \left \{ {{5x+21x-12=4} \atop {y=7x-4}} \right.\ <=>\ \left \{ {{26x=16} \atop {y=7x-4}} \right.<=>\\\ <=>\ \left \{ {{x=\frac{8}{13}} \atop {y=7x-4}} \right.<=>\ \left \{ {{x=\frac{8}{13}} \atop {y=7*\frac{8}{13}-4}} \right. " alt="\left \{ {{5x+3y=4} \atop {\frac{4}{7x-y}=1}} \right.\ <=>\ \left \{ {{5x+3y=4} \atop {7x-y=4}} \right.\ <=>\ \left \{ {{5x+3y=4} \atop {y=7x-4}} \right.\ <=>\\\ <=>\ \left \{ {{5x+3(7x-4)=4} \atop {y=7x-4}} \right.<=>\ \left \{ {{5x+21x-12=4} \atop {y=7x-4}} \right.\ <=>\ \left \{ {{26x=16} \atop {y=7x-4}} \right.<=>\\\ <=>\ \left \{ {{x=\frac{8}{13}} \atop {y=7x-4}} \right.<=>\ \left \{ {{x=\frac{8}{13}} \atop {y=7*\frac{8}{13}-4}} \right. " align="absmiddle" class="latex-formula">
\ \left \{ {{x=\frac{8}{13}} \atop {y=4\frac{4}{13}-4}} \right.<=>\ \left \{ {{x=\frac{8}{13}} \atop {y=\frac{4}{13}}} \right." alt="<=>\ \left \{ {{x=\frac{8}{13}} \atop {y=4\frac{4}{13}-4}} \right.<=>\ \left \{ {{x=\frac{8}{13}} \atop {y=\frac{4}{13}}} \right." align="absmiddle" class="latex-formula">
№2
x²-2x-3=0
(x²-2x+1)-4=0
(x-1)²-4=0
(x-1-2)(x-1+2)=0
(x-3)(x+1)=0
x-3=0 или x+1=0
x=3 x=-1